Synthesis of 1, 2-diketones by mercury-catalyzed alkyne oxidation. Issue 17 (2nd September 2021) - Mei, Xiaochuan; Hu, Weican; Gao, Kexin; Gao, Haotian; Wang, Chaoyang; Qian, Guoying; Rong, Zhouting
Abstract: The first mercury-catalyzed synthesis of 1, 2-diketones by alkyne oxidation has been developed. This inexpensive method extends the potential of mercury catalysis and allows the rapid construction of various 1, 2-diketones and α-carbonyl amides in good yields with high functional group tolerance. Graphical Abstract: UF0001